2016
DOI: 10.1063/1.4945680
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional treatment of nonequilibrium dynamics and higher order elasticity

Abstract: International audienceThis letter presents a three-dimensional model to describe the complex behavior of nonlinear mesoscopic elastic materials such as rocks and concrete. Assuming isotropy and geometric contraction of principal stress axes under dynamic loading, the expression of elastic wave velocity is derived, based on the second-order elastic constants (λ,μ), third-order elastic constants (l, m, n), and a parameter α of nonclassical nonlinear elasticity resulting from conditioning. We demonstrate that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…largest strain amplitude A L ). This effect from the Poisson's ratio was already observed by Lott et al [40]. During the slow relaxation (e.g., at time t 2 ), the induced anisotropy remains.…”
Section: A Longitudinal Motionsupporting
confidence: 69%
See 2 more Smart Citations
“…largest strain amplitude A L ). This effect from the Poisson's ratio was already observed by Lott et al [40]. During the slow relaxation (e.g., at time t 2 ), the induced anisotropy remains.…”
Section: A Longitudinal Motionsupporting
confidence: 69%
“…More recently, Lott et al [40,41] have proposed an extension of Hughes and Kelly's formulation [29] by taking into account the softening of geomaterials under dynamic vibration. This new formulation starts from a volume of material that is small enough to fit within the assumption of continuum mechanics but large enough to contain a relatively large number of defects.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that the linear frequency–strain amplitude dependency observed in hysteretic materials could be modeled in three-dimensional (3D) structures by a single parameter (again, the hysteretic parameter α which relates to the λ n parameters obtained herein). 45 Such a model applies to uniform micro-damaged media (say, isotropically oriented defects), for example, concrete, thermally damaged concrete, and certain rock types. 46 An important finding of these studies 45,46 is that the different slopes λ n at the undamaged state become alike if the precise strain–acceleration conversion for every mode is considered.…”
Section: Discussionmentioning
confidence: 99%
“…45 Such a model applies to uniform micro-damaged media (say, isotropically oriented defects), for example, concrete, thermally damaged concrete, and certain rock types. 46 An important finding of these studies 45,46 is that the different slopes l n at the undamaged state become alike if the precise strain-acceleration conversion for every mode is considered. Herein, we use the relative variations of l n instead of the values of a n to overcome an acceleration to strain the conversion of every mode.…”
Section: Damage Indexesmentioning
confidence: 99%